THE EFFECT OF FOOD ACQUISITION OUTSIDE EXPENDITURES ON THE FOOD SECURITY OF CASSAVA (Manihot utilissima) FARMER HOUSE- HOLDS IN WONOGIRI REGENCY - Saloka, Gilang Aji; Barokah, Umi; Widadie, Fanny (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
As the standard of living increases, the orientation of food consumption shifts from fulfilling intake to fulfilling nutrition. The acquisition of sustenance by means other than farming and government aid can enhance nutritional satisfaction, increasing energy consumption as a measure of food security. This study aimed to assess the impact of food acquisition outside expenditure on the food security of cassava farmer households in Wonogiri Regency. The research was conducted in July 2022. The method of analysis was descriptive quantitative with purposive location determination. A representative sample of 80 households was chosen by applying the proportionate allocation formula. Data were collected using 2 x 24-hour Food Recall. The data analysis in this study focused on three key variables: income, the proportion of food spending, and the Wilcoxon test of energy consumption and food security among farmer households. These variables were examined before and after food acquisition from external sources. The results showed that the average monthly income of farmers was Rp4,985,487.00. The proportion of food expenditure amounted to 33.36 percent. Wilcoxon test showed a significant difference in energy consumption before and after food acquisition outside expenditure. The food security classification of cassava farmer households before the acquisition of food outside expenditure showed that 21.25 percent were classified as food secure, 15 percent were classified as food susceptible, 52.5 percent as food insecure, and 11.25 percent as severely food insecure. After the additional food outside expenditure, the food security classification increased, with 45 percent classified as food secure, 23.75 percent as food susceptible, 25 percent as food insecure, and 6.25 percent as severely food insecure. This finding demonstrates that food utilization from farming and the Non-Cash Food Assistance (Bantuan et al./BPNT) program positively impacts the food security conditions of cassava farmer households in Wonogiri Regency.